Hemingway: ficionista e repórter - Marchezan, Luiz Gonzaga [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
O artigo estuda um conto e uma crônica de Ernest Hemingway, textos sustentados por uma mesma fonte primária: o depoimento que um velho de perto de 76 anos deu ao Hemingway repórter, nas proximidades do rio Ebro, numa frente de combate da Guerra Civil Espanhola. O conto de 1938, “O velho na ponte”, constitui-se, assim, da mesma narrativa de fundação presente, primeiro, na reportagem, também de 1938, “O bombardeio de Tortosa”.

The article studies one of Ernest Hemingways’ short stories and also one of his chronicles, texts supported by one single primary source: the personal account Hemingway reporter was given by a 76-year-old man, in the surroundings of the River Ebro, in one of the Spanish Civil War’s battle fronts. The 1938 short story, Old man at the bridge, constitutes itself from the founding narrative, fi rst present in the article, also dated from 1938, Bombing of Tortosa.
Hemingway: ficcionist and reporter
Keywords: Short store; Chronicle; Description; Fiction; Conto; Notícia; Descrição; Ficção